Who Should Regulate Disruptive Technology?. (6th May 2019) - KOŁACZ, Marta Katarzyna; QUINTAVALLA, Alberto; YALNAZOV, Orlin
Abstract : The primary concern of the present paper is the cost of acquiring information by judges and legislators in the process of regulating new technologies. The paper distinguishes between risky and uncertain applications of technology. A risky technology poses an obvious risk, and the problem before the regulator is one of comparing cost and benefit. We argue that the judiciary, which acquires information gratis from litigants, is better suited to the regulation of risky technologies. Uncertain technologies, on the other hand, can be harmful in ways which cannot be foreseen at the time of the technological innovation. Cost and benefit are incalculable; regulation must instead be based on subjective preferences about the degree of uncertainty that society should tolerate. Legislative law-making is designed with a view to aggregating subjective preferences. Accordingly, uncertain technologies should be regulated through statute.